Pride and prejudice: how trust in institutions may affect nation-building processes in Kazakhstan - Kovyazina, K.T. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2025)
For decades, Kazakhstan has been in search of a national idea that will unite its citizens regardless of their ethnic, religious, and regional origins. A number of programs were introduced to enhance the sense of shared history and belonging to our country; some of them were more successful, some – less. However, there is a clearly overlooked factor that may affect the sense of belonging to a state, whether a citizen feels comfortable and cared for by it. In my article, I want to explore how trust in public institutions may affect the nation-building processes in Kazakhstan. For this aim, I employed the dataset of the World Values Survey for Kazakhstan (7th wave). The results show a positive and statistically significant association between the trust in police, government, and courts, on one side, and the pride in Kazakhstan, and the sense of belonging to a local place of residence, on the other side. The findings also demonstrate that there is a statistically significant negative association between feeling close to a place of residence and the propensity to protest.